Tingkat Pengetahuan Masyarakat tentang Obat Tradisional di Banjar Pejeng Aji Tegalalang Gianyar - Wiradana, Dewa Gde Adi; Dewi Agustini, Ni Putu; Tangkas Suwantara, I Putu; Megawati, Fitria (Usadha, 2023)
Traditional medicine is more widely used by people in rural areas because it is easy to obtain and easy to obtain at relatively cheap prices. Traditional medicine has the ability to cure various kinds of diseases with ingredients that have been trusted for generations. The purpose of this study was to find out how far the level of public knowledge about traditional medicine in Banjar Pejeng Aji, Tegalalang, Gianyar. This research is a type of observational research that is descriptive in nature where data collection techniques are carried out using questionnaires. This research was conducted in Banjar Pejeng Aji, Tegalalang, Gianyar with a population of 254 heads of families and a sample of 80 respondents with an age range of 17-65 years was obtained. The data obtained from the research is then processed by calculating the percentage value of the respondents' answers. The results of the analysis of the questionnaire data obtained from 80 respondents showed that the level of public knowledge in Banjar Pejeng Aji, Tegalalang, Gianyar was in the Good category, where out of 80 respondents who were the research sample 75 respondents (93.75%) respondents had good knowledge, 5 respondents (6.25%) had sufficient knowledge and 0 (0%) respondents had less knowledge